Designing a Digital Flipbook for Arabic Writing Skills: A Design and Development Study on Family and Home Themes - Afril, Rezkya; Ritonga, Mahyudin; Triana, Hetti Waluati (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
This study examines the design process in developing Digital Flipbook-based learning media for teaching maharah al-kitabah to tenth-grade students of Madrasah Aliyah. The need for this development arises from the limited availability of interactive and structured writing materials that align with contemporary digital learning environments. Using the ADDIE development model, this research focuses specifically on the Design stage as the conceptual foundation for producing effective learning media. The stage involves formulating learning objectives, selecting appropriate content for the theme “Family and Home,” and organizing the material into a coherent instructional structure. The resulting prototype consists of an introductory section, core learning materials, writing exercises, and a Student Worksheet integrated to support guided practice. The findings indicate that a systematically designed prototype can provide a clear framework for subsequent development and has the potential to enhance student engagement in writing activities. This design serves as the basis for the next Development stage, where the prototype will be transformed into a fully functional Digital Flipbook.